Modelling and optimization of phase change materials (PCM)-based passive cooling of solar PV panels in multi climate conditions - Durez, Asif; Ali, Muzaffar; Waqas, Adeel; Nazir, Kamran; Kumarasamy, Sudhakar (Frontiers in Energy Research, 2023)
To address the increasing energy demand, replacing conventional energy systems with nonconventional resources like solar power generation is crucial. Photovoltaic (PV) panels play a significant role in harnessing solar energy and converting it into electrical power. However, the solar cells' temperature dramatically influences the panel's performance, particularly in hot climates. In this study, a detailed mathematical model is developed and conducted simulations using three different phase change materials (PCMs) -RT21, RT35, and RT44 -integrated with PV panels in various climate conditions worldwide during the summer season. An optimization model is also created using MATLAB and a genetic algorithm to identify the most suitable PCM for specific climate zones. The findings revealed that incorporating PCM resulted in a surface temperature reduction of PV panels, leading to a 6% increase in efficiency and a 16% boost in electrical output. Specifically, when using a PCM with a melting point of 21°C, the maximum cell temperature during summer operation decreased from 65°C to 38°C. Similar temperature reductions were observed when using PCMs with melting points of 35°C and 44°C. Current 2 analysis demonstrates that the correct selection of a phase change material can decrease panel temperature by approximately 39% in June. Furthermore, PCM with a melting point of 21°C exhibited the best outcomes in terms of maximum electrical performance, efficiency, and PV cell temperature reduction.